466. OUTCOME OF NIVOLUMAB FOR UNRESECTABLE ADVANCED OR RECURRENT ESOPHAGEAL CANCER IN OUR INSTITUTION. (24th September 2022) - Tabuchi, Satoshi; Takano, Yuki; Ochiai, Shigeto; Gunji, Takahiro; Kobayashi, Toshimichi; Suzumura, Hirofumi; Shigoka, Masatoshi; Chiba, Naokazu; Hidaka, Eiji; Kawachi, Shigeyuki
Abstract: In recent years, drug therapy for esophageal cancer has seen rapid progress, including immune checkpoint inhibitors. Guidelines for the treatment of esophageal cancer recommend nivolumab as second-line therapy. We report the results of nivolumab for unresectable advanced or recurrent esophageal cancer in our institution, including the cases that responded to the therapy. We analyzed 12 patients (male: female = 10:2, median age: 67 years) treated with nivolumab for unresectable advanced or recurrent esophageal cancer between March 2020 and March 2022. The status of treatment, response rate, adverse effects, and conversion rate to next line were analyzed for these patients. The median follow-up period was 4.2 months, and the median number of treatment cycles was 5 (2-41). Response rate was 17%, and disease control rate was 42%. Adverse effects included one case (8%) of severe diarrhea, considered ir-AE. The patient was treated with steroids. The rate of conversion to next-line treatment was 17% (2 cases). Nivolumab for esophageal cancer has a good prognosis in patients who respond to it. In addition, it is important to pay attention to ir-AE, perform imaging and physical examinations, and evaluate accurately and treat quickly.